PENGARUH DOSIS PUPUK KANDANG KAMBING TERHADAP HASIL TANAMAN SAWI (Brassica juncea L.) - Lisda, Lisda; Idham, Idham (Fakultas Pertanian, Universitas Tadulako, 2023)
The aim of the study was to determine the effects of different amounts of goat manure on the growth of Chinese mustard (Brassica juncea L.) plant. The research was carried out at the Green House of the Faculty of Agriculture at Tadulako University, Palu. The study took place from February to April 2020 and used a Randomized Block Design (RBD) with five treatments. The treatments involved varying doses of goat manure: no manure (P0), 5 tons/ha (P1), 10 tons/ha (P2), 15 tons/ha (P3), and 20 tons/ha (P4). Each treatment was replicated 3 times, resulting in 21 experimental units. The findings revealed that the P4 treatment resulted in largest plant height, and leaf number and leaf area size at 28 days after sowing.